Pengaruh Teknik Biblioterapi Terhadap Kesadaran Diri Siswa - Gunawan, I Made; Wulandari, Juwita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
Self awareness is a condition where the individual is able to realize the advantages and disadvantages possessed, able to realize the interests that have to be channeled properly. Self-awareness and self-knowledge leads to quality life stages, not only in socializing and interacting with others, but also to direct and develop oneself, to help career education planning, to solve social personal problems realistically, to adapt to changes in life. The purpose of the study was to determine the effect of Biblioterapi technique on self-awareness of the students of class XI of Computer And Network Technology (TKJ) SMK Negeri 1 Tanjung Kabupaten Lombok Utara. The data collection methods used in this study in the form of a questionnaire as the main method while the interview, documentation and observation as a complement method, data analysis using t-test formula. The results of this research data analysis obtained 8.179 and after consultation with ttable at the level of significance 5% with d.b 11 obtained 2.201. This means that t count is greater than ttable (8.179> 2.201). So it can be concluded that there is influence of Biblioterapi technique to self-awareness of class XI students Computer And Netwo rk Technology (TKJ) SMK Negeri 1 Tanjung Kabupaten Lombok Utara.